2014
DOI: 10.1007/s00520-014-2514-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors’ perceived need for supportive care and their attitude towards self-management and eHealth

Abstract: The perceived need for supportive care including healthy lifestyle programs was high, and in general, cancer survivors had a positive attitude towards self-management and eHealth. Need and attitude were associated with sociodemographic and clinical variables and quality of life. Therefore, a tailored approach seems to be warranted to improve and innovate supportive care targeting cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
155
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(177 citation statements)
references
References 43 publications
18
155
3
1
Order By: Relevance
“…The preference for a blended care option corroborated findings from studies among cancer patients in general [21] and neuro-oncology patient/caregiver populations in particular [22]. Cancer survivors (N = 212) viewed eHealth applications favorably, with 48% indicating that they would find the option to self-monitor their side-effects and symptoms attractive [21].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The preference for a blended care option corroborated findings from studies among cancer patients in general [21] and neuro-oncology patient/caregiver populations in particular [22]. Cancer survivors (N = 212) viewed eHealth applications favorably, with 48% indicating that they would find the option to self-monitor their side-effects and symptoms attractive [21].…”
Section: Discussionsupporting
confidence: 58%
“…Cancer survivors (N = 212) viewed eHealth applications favorably, with 48% indicating that they would find the option to self-monitor their side-effects and symptoms attractive [21]. A feasibility study testing a Danish brain tumor website among brain tumor patients and caregivers furthermore showed that especially caregivers appreciated the option to contact health care professionals online [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, only a few studies have identified the unmet needs of cancer survivors (Jansen, van Uden‐Kraan, van Zwieten, Witte, & Verdonck‐de Leeuw, 2015; Kanera, Bolman, Willems, & Mesters, 2016; Pauwels, Charlier, De Bourdeaudhuij, Lechner, & Van Hoof, 2013; Willems et al., 2016a,b). For our two studies (Kanera, Bolman, Mesters, et al., 2016; Willems et al., 2016a), the validated CaSUN was regarded as the most appropriate general questionnaire to specifically investigate the unmet needs of cancer survivors (Bender et al., 2012; Brennan, Butow, Spillane, & Boyle, 2016; Geller et al., 2014; Harrison et al., 2011; Hodgkinson, Butow, Fuchs, et al., 2007; Hodgkinson, Butow, Hunt, et al., 2007; Rowlands, Janda, McKinnon, Webb, & Beesley, 2015; Smith et al., 2013; Urbaniec, Collins, Denson, & Whitford, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is no single solution to facilitate positive behavior change across a population of people with cancer in active treatment, however, the innovative use of technology may benefit a proportion of the population. Patients with cancer who have tertiary education, who are undergoing intensive treatment and those who report reduced Health Related Quality of Life express a more positive perception of and openness to use of WPs [8,26]. Despite an overall positive perception of eHealth interventions there are varying perceptions of their usability from both patients and clinicians, despite demonstrated benefits to self-management and outcomes [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Research involving patients with a history of cancer indicates most have positive attitudes towards the use of eHealth methods in their management and care of cancer [8]. The use of WPs by patients with a chronic condition such as cancer is a growing area of eHealth research.…”
Section: Ehealth and Web-based Portalsmentioning
confidence: 99%